2021
DOI: 10.1002/wer.1650
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dissolved organic matter on carbonyl sulfide and carbon disulfide formation from dimethyl sulfide during sunlight photolysis

Abstract: Carbonyl sulfide (COS) and carbon disulfide (CS2) are important atmospheric gases photochemically generated from organic sulfur precursors in sunlit natural waters. This study examined these processes by evaluating COS and CS2 photoproduction from dimethyl sulfide (DMS) in the presence of dissolved organic matter (DOM). DOM was added because it photochemically produces various reactive intermediates (3CDOM*, •OH, 1O2, and H2O2) potentially involved in these reaction pathways. DMS‐amended synthetic waters at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Previous research has shown that cysteine does not form COS via direct photolysis due to the negligible absorption of sunlight by cysteine, but is more likely to be converted by indirect photolysis (Gharehveran et al, 2020). Prior research has suggested that cysteine can react with a variety of ROS (e.g., •OH, H 2 O 2 , 1 O 2 , and 3 CDOM*) (Chu et al, 2016;Trujillo et al, 2016), while 3 CDOM* and •OH may be involved in the formation of COS (Flock et al, 1997;Gharehveran et al, 2020). In the current study, when the samples were left in dark conditions for 2 hr again, COS concentrations exhibited a slow decline.…”
Section: Effect Of Nitrate On Cos Production Under Simulated Sunlightsupporting
confidence: 45%
See 4 more Smart Citations
“…Previous research has shown that cysteine does not form COS via direct photolysis due to the negligible absorption of sunlight by cysteine, but is more likely to be converted by indirect photolysis (Gharehveran et al, 2020). Prior research has suggested that cysteine can react with a variety of ROS (e.g., •OH, H 2 O 2 , 1 O 2 , and 3 CDOM*) (Chu et al, 2016;Trujillo et al, 2016), while 3 CDOM* and •OH may be involved in the formation of COS (Flock et al, 1997;Gharehveran et al, 2020). In the current study, when the samples were left in dark conditions for 2 hr again, COS concentrations exhibited a slow decline.…”
Section: Effect Of Nitrate On Cos Production Under Simulated Sunlightsupporting
confidence: 45%
“…We selected cysteine as a model compound due to: (a) its ability to form considerable levels of COS and CS 2 compared to other precursors; and (b) it does not undergo direct photolysis. In addition, previous photochemical studies on COS have also extensively selected cysteine as a representative of DOS (Gharehveran et al, 2020;Gharehveran & Shah, 2018;Ossola et al, 2019). We first investigated the production of COS in seawater containing cysteine at room temperature (24°C) in dark conditions.…”
Section: Radiation Wavelength Dependence For Cos Productionmentioning
confidence: 99%
See 3 more Smart Citations